PENGARUH KEPUASAN KERJA TERHADAP TURNOVER INTENTION MELALUI MEDIASI KOMITMEN ORGANISASIONAL PADA PT. CIOMAS ADISATWA DI DENPASAR - Indrayanti, Desak Putu; Riana, I Gede (E-Jurnal Manajemen, 2016)
The purpose of this study was to determine the effect of job satisfaction on turnover intention through the mediation of organizational commitment at PT. Ciomas Adisatwa in Denpasar . The high level of out employees of the company will lead to increasing costs incurred by the company to the employee recruiting and retraining costs. This research was conducted at PT. Ciomas Adisatwa. The number of respondents who were taken as many as 34 employees by using census method. Data collected through questionnaires using Likert scale. The analysis technique used is path analysis. Based on the analysis found that job satisfaction is positive and significant effect on organizational commitment. Job satisfaction and significant negative effect on turnover intention. Organizational commitment and significant negative effect on turnover intention. Job satisfaction and significant negative effect on turnover intention through organizational commitment.
Keywords: Job Satisfaction, Organizational Commitment, Turnover Intention